PENGARUH KESADARAN LINGKUNGAN TERHADAP NILAI PERUSAHAAN DENGAN EFISIENSI INVESTASI SEBAGAI VARIABEL INTERVERNING - Silvina Septiana; Idrianita Anis (STMIK Widuri Jakarta, 2024)
This research was conducted to analyze the influence of environmental awareness on firm value with investment efficiency as an interverning variable on the Indonesia Stock Exchange in the period 2020 to 2022. The population in this study was 38 companies in the Consumer Goods Industry Sector on the Indonesia Stock ExchangeThe population in this study was 38 Consumer Goods Industrial Sector companies on the Indonesian Stock Exchange. This research is quantitative research, namely by collecting data using secondary data. The data in this research was obtained from financial report data on the official website of the Indonesia Stock Exchange (BEI) (www.idx.co.id The results of this research show that the environmental awareness variable have a positive influence on firm value. Environmental awareness have no influence on firm value. And investment efficiency is able to mediate the effect of environmental awareness variable positively on firm value.